Relaxation phenomena in poly(methyl methacrylate) - V. A. Lomovskoy (Тонкие химические технологии, 2015)
Spectra of internal friction for plasticized and non-plasticized poly(methyl methacrylate) (PMMA) are obtained by dynamic methods of external distortion effect within a frequencies range from 10-2 to 103 Hz and within a temperature range from -50 up to +250°С. Areas of local non-elasticity are revealed, and mechanisms of dissipative losses occurring in various temperature areas of the spectra are determined. Calculation of physico-chemical characteristics is made for each of the revealed relaxation processes, and the dependence of these characteristics on molecular mass and various doses of gamma and neutron irradiation is determined. Special temperature points are revealed in the area of structural vitrification, and possible causes of their emergence are discussed considering model representations of the fluctuation theory of density. Methods of analysis and assessment of the microinhomogeneity degree of PMMA structure are considered using the fractional-exponential Kohlrausch function in the Boltzmann-Volterra integral equation as relaxation memory function. Theoretical analysis of “Deborah number” concept application for the description of inelasticity processes of relaxation origin is made using the phenomenological generalized Maxwell model.